2017
DOI: 10.30870/jppm.v10i2.2027
|View full text |Cite
|
Sign up to set email alerts
|

Tahap Perkembangan Kognitif Matematika Siswa SMP Kelas Vii Berdasarkan Teori Piaget Ditinjau Dari Perbedaan Jenis Kelamin

Abstract: This study aims to examine the suitability of Piaget's cognitive development stage to grade VII students in Karawang regency, whether it has arrived at the formal operation stage, as described in Piaget's theory. The subjects of this study were 32 students with an age between 12 to 16 years. This study uses the instrument of Test of Logical Operations (TLO) in mathematics. TLO consists of 14 questions and students are given time to answer all questions for 45 minutes. The results showed 41.18% of male students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
3
0
8
Order By: Relevance
“…Based on the data above, with a ratio of 3: 7 female and male students, it can be concluded that the logical thinking stages of male and female students have the same tendency, namely the formal thinking stage. In line with Aini and Hidayati in their research, it shows that male and female students have reached the formal stage where women are more dominant in reaching the formal stage (Aini & Hidayati, 2017). The formal logical thinking stage is the highest stage of logical thinking.…”
Section: Students' Logical Thinking Abilitysupporting
confidence: 79%
“…Based on the data above, with a ratio of 3: 7 female and male students, it can be concluded that the logical thinking stages of male and female students have the same tendency, namely the formal thinking stage. In line with Aini and Hidayati in their research, it shows that male and female students have reached the formal stage where women are more dominant in reaching the formal stage (Aini & Hidayati, 2017). The formal logical thinking stage is the highest stage of logical thinking.…”
Section: Students' Logical Thinking Abilitysupporting
confidence: 79%
“…Tahap operasi formal merupakan tahap dimana anak mampu berpikir logis, berpikir dengan pemikiran teoritis formal berdasarkan proposisi-proposisi dan hipotesis, dan mampu mengambil kesimpulan terlepas dari apa yang diamati saat itu (Suparno, 2001). Individu yang berada pada tahap operasi formal apabila dihadapkan kepada suatu masalah, dapat merumuskan dugaan-dugaan atau hipotesis-hipotesis tersebut (Aini & Hidayati, 2017). Dengan kata lain, siswa SMP dengan usia 11-15 sudah mampu menganalisa dengan logika dan mampu mengerti dengan cara pemikiran abstrak.…”
Section: Pendahuluanunclassified
“…Salah satu cara yang biasa digunakan yaitu dengan mengkaji teori-teori perkembangan kognitif yang telah ada. Salah satu teori yang sering digunakan dalam membahas teori perkembangan kognitif yaitu teori yang dikembangkan oleh Jean Piaget seorang psikolog yang juga ahli biologi kelahiran Swiss pada tahun 1896 (Aini & Hidayati, 2017). Perkembangan kognitif peserta didik merupakan hal dasar yang penting untuk diketahui, sehingga nantinya guru atau pendidik dapat menyusun materi pembelajaran matematika dan menggunakan model pembelajaran yang sesuai dengan kondisi kognitif peserta didiknya.…”
Section: Pendahuluanunclassified
“…Teori kontruktivisme mempertanyakan apa dan bagaimana peran guru yang baik dan peran murid yang sesungguhnya dalam menggeluti ilmu pengetahuan. Tidak ketinggalan, metode penelitian Piaget banyak mewarnai penelitian pemikiran anak (Aini & Hidayati, 2017).…”
Section: Pendahuluanunclassified